Digenean parasites of the Neotropic Cormorant, Phalacrocorax brasilianus (Gmelin, 1789) (Aves: Phalacrocoracidae) from Argentina: distribution extension and new host records - Drago, Fabiana Beatriz (2011)
Thirteen specimens of Phalacrocorax brasilianus (Gmelin, 1789) from three areas of the Chaqueña Subregion of Argentina were examined for digeneans. Ten species were found: four diplostomids (Austrodiplostomum mordax, A. ostrowskiae, Tylodelphys adulta and Hysteromorpha triloba), three echinostomatids (Drepanocephalus spathans, Paryphostomum segregatum, and P. parvicephalum), one strigeid (Strigea falconis brasiliana), one psilostomid (Ribeiroia ondatrae) and one prosthogonimid (Prosthogonimus ovatus). Tylodelphys adulta and S. f. brasiliana are reported for the first time as parasites of P. brasilianus and new geographical records are presented.